The Possibility of a Gender-Transcendent God: Taking Macmurray Forward - Mclntosh, Esther (Feminist theology, 2007)
This paper borrows from philosopher John Macmurray's insightsin order to advance work in feminist theology relating to perceptions of God. Mac-murray argues that we cannot have an adequate concept of a personalGod, if our concept of the human person is inadequate.He asserts that we are persons by virtue of our agency and our personal relationships; hence, the growth and development of persons requires communities of equals. Beliefin God, then, is an attitude expressed through behaviour that creates and sustains such communities. As feminist theologians indicate, a‘male’ God is a stumbling block to equality; yet, thealogy remains on the periphery of mainstream academic and Christian circles. Hence, this paper sets the groundwork for a truly gender-transcendent concept of God, examining some contemporary language liturgies and employing Macmurray's portrayal of a supreme agent, in an attempt to resolve the main problems encountered by inclusive God-language.